Stepped Frequency Pulse Frequency Diverse Array Radar for Target Localization in Angle and Range Domains - Ming Tan; Chun-yang Wang; Zhi-hui Li; Xin Li; Lei Bao (International Journal of Antennas and Propagation)
Unlike phased array bringing angle-dependent and range-independent beamforming, a new kind of radar system called frequency diverse array (FDA) has been widely used for its ability to generate angle-range-dependent beampattern, which provides a broad prospect of radar application. Nevertheless, FDA beampattern is coupling in the angle and range responses, which results in the difficulty for FDA to differentiate the target in two domains simultaneously. In this paper, a stepped frequency pulse FDA (SFP-FDA) radar is proposed to wipe off the angle-range coupling in FDA and improve the target’s angle and range localization accuracy. Compared to the double-pulse FDA, the proposed system can achieve a better performance in range resolution and multitarget identification. The Cramér-Rao lower bound (CRLB) is derived and used to analyze the performance of the proposed system and double-pulse FDA radar. Numerical results are implemented to verify the validity of the proposed scheme.